Clinical Characteristics of Invasive Pneumococcal Disease of the Mucoid Phenotype: A Case Series - Takamatsu, Akane; Matsuzaka, Suguru; Kodama, Fumihiro (Kansenshōgaku zasshi, 2017)
Streptococcus pneumoniae is a gram-positive coccus that causes invasive and non-invasive pneumococcal diseases. Invasive pneumococcal disease (IPD) is defined as an infection confirmed by the isolation of S. pneumoniae from a normally sterile site. IPD has a high mortality rate of around 20% in adults. Colonies of S. pneumoniae show various morphological features which include a mucoid appearance. The production of large amounts of capsular polysaccharide gives colonies of S. pneumoniae their mucoid appearance. This is thought to be a mechanism of microbial escape from phagocyte killing, leading to strong pathogenicity despite their high susceptibility to antibiotics. To our knowledge, the clinical characteristics of patients with mucoid IPD are unknown. We retrospectively analyzed the records of adult patients with IPD of the mucoid phenotype at Teine Keijinkai Hospital, Hokkaido, Japan, between 2009 and 2015. Seven patients (six males) with age range between 62 and 80 years were diagnosed as having mucoid IPD during the study period. Two patients had a history of malignancy and diabetes mellitus respectively, and six patients were living independently. No patients were previously vaccinated with pneumococcal vaccine. Six patients had clinical manifestations of pneumonia; one patient had multiple concomitant complications of mastoiditis, meningitis, and prosthetic joint infection. All isolates were isolated from blood. All isolates were susceptible to beta-lactam antibiotics, while six isolates were resistant to macrolides and chloramphenicol. Based on the Quellung reaction and real-time polymerase chain reaction (PCR) results, one isolate of mucoid phenotype was confirmed as serotype 3 with the penicillin binding protein gene of pbp2x and the macrolide resistant gene of ermB. Although all patients received appropriate antibiotics based on susceptibility testing, four patients required mechanical ventilation and vasopressors. One patient had neurological sequelae (hypacusis) and two patients died during the course of hospitalization. This case series suggests that mucoid IPD can occur in immunocompetent hosts and can cause high mortality. Since most of the mucoid phenotype of S. pneumoniae are serotype 3, widespread use of pneumococcal vaccine is important to prevent morbidity and mortality associated with IPD.